If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6-9p=-5p-9-9
We move all terms to the left:
6-9p-(-5p-9-9)=0
We add all the numbers together, and all the variables
-9p-(-5p-18)+6=0
We get rid of parentheses
-9p+5p+18+6=0
We add all the numbers together, and all the variables
-4p+24=0
We move all terms containing p to the left, all other terms to the right
-4p=-24
p=-24/-4
p=+6
| 3k+2=41 | | 2x^{2}+6x-20=0 | | -h+6=-2h+10 | | 29.2/8=x/4 | | 3x+26=5x-20 | | p-6/14=-1 | | -17=19n=-150 | | 17=-3(23-m)+2(m-2) | | -2+m/9=-3 | | 6i-3=-18+i | | p+7/3=7 | | -8x-18=-274 | | 47=31-4(x-2) | | p+6/3=3 | | 16x+19=595 | | x-5/6=-1/6 | | n=9/10=-4 | | p–5=-2 | | 22=2h+10 | | -4.5+3=2-8.5x | | B.2/3b-1/3b=4/3 | | 39=26-b | | 7l-4=2l+16 | | -66=-3(m+5) | | 15=-5t^2+20t+1 | | 4(-x+2)=x-5+3 | | 5b+5=14+2b | | -3/7h=42 | | 5(2t-3)-7.5t=0.5(12-0) | | x=8,2x-10 | | -9(-6+b)=135 | | 30-n=59 |